How to use the International Classification of Functioning, Disability and Health as a reference system for comparative evaluation and standardized reporting of rehabilitation interventions - Stucki, Gerold; Pollock, Alex; Engkasan, Julia Patrick; Selb, Melissa (Edizioni Minerva Medica, 2019)
Rehabilitation aims to optimize functioning of persons experiencing functioning limitations. As such the comparative evaluation of rehabilitation interventions relies on the analysis of the differences between the change in patient functioning after a specific rehabilitation intervention versus the change following another intervention. A robust health information reference system that can facilitate the comparative evaluation of changes in functioning in rehabilitation studies and the standardized reporting of rehabilitation interventions is the International Classification of Functioning, Disability and Health (ICF). The objective of this paper is to present recommendations that Cochrane Rehabilitation could adopt for using the ICF in rehabilitation studies by: 1) defining the functioning categories to be included in a rehabilitation study; 2) specifying selected functioning categories and selecting suitable data collection instruments; 3) examining aspects of functioning that have been documented in a study; 4) reporting functioning data collected with various data collection instruments; and 5) communicating results in an accessible, meaningful and easily understandable way. The authors provide examples of concrete studies that underscore these recommendations, whereby also em-phasizing the need for future research on the implementation of specific recommendations, e.g. in meta-analysis in systematic literature reviews. Furthermore, the paper outlines how the ICF can complement or be integrated in established Cochrane and rehabilitation research structures and methods, e.g. use of standard mean difference to compare cross-study data collected using different measures, in developing core outcome sets for rehabilitation, and the use of the PICO model. © 2019 EDIZIONI MINERVA MEDICA.